INCLUSION OF SCHOOL STUDENTS TARGET OF SPECIAL EDUCATION: HOW IS THE PEDAGOGICAL WORK OF THE TEACHER IN ELEMENTARY SCHOOL? - Silva, Suzana Sirlene da [UNESP]; Carbone Carneiro, Relma Urel [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
This article reports a research developed with teachers working in mainstream schools and having students with disabilities included in the classroom. The central problem of the study versa and aims to verify how you are giving the teaching/educational work with target group students of special education in the common room. For this, it constitutes a qualitative study of exploratory and descriptive, using as a data collection tool free questionnaire and open questions. Participants were five teachers from public and private schools. To analyze the data was used content analysis and the results revealed that the teachers are new professionals, and teachers plying the period of work, not presenting courses in the field of special education; work from the naturalization of the student, tailored and differentiated activities, encountering difficulties in accessibility and concentration of this student in the tasks presented, do not consider that there is a collaborative work between them and the specialist teachers, but agree that the inclusion of the target group of special education student brings gains in the overall context, and is teaching the important part for real academic inclusion of the pupils concerned.
Keywords: Special education; School inclusion; teaching work; Pedagogical practices